1995
DOI: 10.1007/bf02564736
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic correction of vesicoureteral reflux in patients with neurogenic bladder dysfunction

Abstract: Transurethral injection of Teflon paste (TUI) was carried out in 24 ureters of 16 patients with vesicoureteral reflux (VUR) secondary to neurogenic bladder dysfunction at an age ranging from 4 to 77 years, and the results were compared with those of conventional open surgery. During the mean follow-up period of 20.1 months, reflux disappeared in 19 ureters (79%), so that the success rate of endoscopic operation was considered to be satisfactory as compared with that of conventional open surgery, in which reflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It has a success rate of 60-80%, depending on the substance used and the degree of reflux corrected [3]. In some cases multiple injections are needed, but its safety and long-term effectiveness are controversial [4,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…It has a success rate of 60-80%, depending on the substance used and the degree of reflux corrected [3]. In some cases multiple injections are needed, but its safety and long-term effectiveness are controversial [4,[12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…7,14-19 Sugiyama et al, reported 79% success following Teflon paste injection in 16 patients with neurogenic bladder dysfunction. 20 Shah et al, reports 77.2% success after single or repeat injection in similar population. 8 Polackwick et al, in a series of 12 patients with neurogenic bladder showed that the success reduced to 35% at 4.5 years (58% at 12 months).…”
Section: Discussionmentioning
confidence: 93%